2014
DOI: 10.1016/j.neurobiolaging.2014.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological intervention for memory decline

Abstract: Non-pharmacological intervention of memory difficulties in healthy older adults, as well as those with brain damage and neurodegenerative disorders, has gained much attention in recent years. The two main reasons that explain this growing interest in memory rehabilitation are the limited efficacy of current drug therapies and the plasticity of the human central nervous and the discovery that during aging, the connections in the brain are not fixed but retain the capacity to change with learning. Moreover, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 173 publications
(190 reference statements)
1
0
0
Order By: Relevance
“…This is consistent with research evidences which suggest that interventions promoting neural plasticity can induce significant cognitive gains especially in patients with mild AD [106]. These improvements have involved various non-invasive, or non-pharmacological interventions which have increasingly gained attention in recent years [107,108], such as in virtual reality, 3D simulation technologies and intelligent environments [43,109]. Furthermore, investigators have revealed that optimizing personal control of spaces by patients, contributes to their emotional comfort which facilitates the therapeutic process of hospitalized patients [110].…”
Section: Non-invasive Technological Interventions For Improving Clinisupporting
confidence: 87%
“…This is consistent with research evidences which suggest that interventions promoting neural plasticity can induce significant cognitive gains especially in patients with mild AD [106]. These improvements have involved various non-invasive, or non-pharmacological interventions which have increasingly gained attention in recent years [107,108], such as in virtual reality, 3D simulation technologies and intelligent environments [43,109]. Furthermore, investigators have revealed that optimizing personal control of spaces by patients, contributes to their emotional comfort which facilitates the therapeutic process of hospitalized patients [110].…”
Section: Non-invasive Technological Interventions For Improving Clinisupporting
confidence: 87%